A case of collision tumor or transdifferentiation between malignant melanoma and leiomyosarcoma - Jamshaid Ul-Mulk; Helle Rasmussen; Line Breiting; Elsebeth Siim (Wolters Kluwer Medknow Publications, 2012)
A 73-year-old woman was referred to the hospital due to a pigmented, asymptomatic nevus on her right arm that had changed in size and color. The histopathological examination showed a superficial spreading malignant melanoma, Clark level III, 2.26 mm in thickness. Two years later, the patient presented a 10 cm rapidly growing mass in her right axilla. The mass in the axilla measured 12.5 ΄ 9 ΄ cm. It revealed a lymph node metastases with a tumor growth composed of two different contiguous morphological and immunohistochemical components, respectively, melanosomes and leiomyosarcoma. The combination of a melanocytic nevus with other tumor of epidermal or adnexal origin has been described before, but still the co-existence of two different neoplasms within a lesion is still uncommon. The most common combination is basal cell carcinoma and melanocytic nevus or one of them together with a seborrheic keratosis. There have also been occasional reports of rhabdomyosarcomatous differentiation. However, mesenchymal differentiation, and in this case leiomysarcoma, with formation of heterologous elements in melanocytic tumor is very rare. Another plausible explanation may be that malignant melanoma cells could have transdifferentiated into a leiomyosarcomatoid phenotype with resulting metastases of either type. Malignant melanomas have shown a wide variety of cytological changes and can mimic carcinomas, lymphomas, and sarcomas. Spindle cell melanomas commonly simulate spindle cell carcinomas. It has also been documented that desmoplastic melanomas can change into fibroblastic, Schwannian, and myofibroblastic differentiation.